HERCing: Structural and Functional Relevance of the Large HERC Ubiquitin Ligases - García-Cano, Jesús; Martinez-Martinez, Arturo; Sala-Gaston, Joan; Pedrazza, Leonardo; Rosa, Jose Luis (Frontiers in Physiology, 2019)
Homologous to the E6AP carboxyl terminus (HECT) and Regulator of Chromosome Condensation 1 (RCC1)-like domain-containing proteins (HERCs) belong to the superfamily of ubiquitin ligases. HERC proteins are divided into two subfamilies, Large and Small HERCs. Despite their similarities in terms of both structure and domains, these subfamilies are evolutionarily very distant and result from a convergence phenomenon rather than from a common origin. Large HERC genes, HERC1 and HERC2, are present in most metazoan taxa. They encode very large proteins (approximately 5000 amino acid residues in a single polypeptide chain) that contain more than one RCC1-like domains as a structural characteristic. Accumulating evidences show that these unusually large proteins play key roles in a wide range of cellular functions which include neurodevelopment, DNA damage repair and cell proliferation. To better understand the origin, evolution and function of the Large HERC family, this minireview provides with an integrated overview of their structure and function and details their physiological implications. This study also highlights and discusses how dysregulation of these proteins is associated with severe human diseases such as neurological disorders and cancer.